Bahasa Dalam Konteks Sosial (Peristiwa Tutur Dan Tindak Tutur) - Utami, Rizka; Rizal, Muhammad (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2022)
The interactions that take place among community members are closely related to the use of language as a communication tool to express thoughts, feelings and desires. This communication process will form speech events and speech acts. This study aims to examine the concept of language in a social context from the aspect of speech events and speech acts. The research method used is library research with data analysis method in the form of content analysis method. The results of the study show that speech events have eight components that must be met, known as SPEAKING, namely; S (Setting and Scene), P (Participants), E (End : Purupose and Goal), A (Act Sequences), K (Key : Tone or Spirit of Act), I (Instrumentalities), N (Norm of Interaction and Interpretation ) and G (Genres). The speech acts are classified based on the purpose of the speech consisting of constative and performative and based on the type of speech consisting of locutionary, illocutionary, perlocutionary.